DRAMATURGY AS PART OF THE LIFE OF FEMALE COMMERCIAL SEX WORKERS : DRAMATURGI SEBAGAI BAGIAN DALAM KEHIDUPAN WANITA PEKERJA SEKS KOMERSIAL - Ratifika Dewi Irianto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Nightlife approaching Bandung city is a good time for commercial sex workers. Stasion became one that often came as a safe transaction for them because the comfort place for them. As for the life presented by these sex workers, this reflects the existence of backstage life and front stage. In this study using a qualitative approach to see how the dramaturgy performed on women sex workers. The presence of contradictions in the life of the backstage and the front stage of their lives does not affect on their religious life. In this research will represent the contradiction of their usual life and nightlife as commercial sex workers.